Control of the oceanic heat content of the Getz‐Dotson Trough, Antarctica, by the Amundsen Sea Low - Dotto, TS; Naveira Garabato, AC; Wåhlin, AK; Bacon, S; Holland, PR; Kimura, S; Tsamados, M; Herraiz‐Borreguero, L; Kalén, O; Jenkins, A (American Geophysical Union (AGU), 2020)
The changing supply of warm Circumpolar Deep Water (CDW) to the West Antarctic continental shelf is responsible for the basal melting and thinning of the West Antarctic ice shelves that has occurred in recent decades. Here we assess the variability in CDW supply, and its drivers, from a multiyear mooring deployed in, and a regional ocean model spanning, the Getz‐Dotson Trough, Amundsen Sea. Between 2010 to 2015, the CDW within the trough underwent a pronounced cooling and freshening, associated with changes in thermohaline properties on isopycnals. Variability in the rate of CDW inflow is controlled by local wind forcing of a shelf break undercurrent, which determines the hydrographic properties of inflowing CDW via tilting of density surfaces above the continental slope. Local wind is coupled to the Amundsen Sea Low (ASL) low‐pressure system, which is modulated by large‐scale climatic modes via atmospheric teleconnections. For the period analyzed, a deeper ASL was associated with westward wind anomaly at the shelf break. Changes in the sea surface slope decelerated the shelf break undercurrent, resulting in less heat accessing the continental shelf and, consequently, a cooling of the Getz‐Dotson Trough. Therefore, the present work suggests that the fate of the West Antarctic ice shelves is closely tied to the future evolution of the ASL.